Antioxidant activity of cod (Gadus morhua) protein hydrolysates: Fractionation and characterisation of peptide fractions. (1st August 2016) - Sabeena Farvin, K.H.; Andersen, Lisa Lystbæk; Otte, Jeanette; Nielsen, Henrik Hauch; Jessen, Flemming; Jacobsen, Charlotte
Highlights: In a cod protein hydrolysate the fraction <3 kDa contained the highest amount of free amino acids. All sub-fractions showed high Fe 2+ chelating activity. Peptides <600 Da with His and Tyr dominated in fractions with high radical-scavenging activity. Peptides rich in Arg, Tyr and Phe showed significantly higher reducing power. Abstract: This study aimed to characterise peptide fractions (>5 kDa, 3–5 kDa and <3 kDa) with antioxidative activity obtained from a cod protein hydrolysate. The free amino acids in all fractions were dominated by Ala, Gly, Glu and Ser. The total amino acid composition had high proportions of Lys, Ala and Glu. The 3–5 kDa and <3 kDa fractions were further fractionated by size exclusion chromatography. All sub-fractions showed high Fe 2+ chelating activity. The DPPH radical-scavenging activity of the 3–5 kDa fraction was exerted mainly by one sub-fraction dominated by peptides with masses below 600 Da. The DPPH radical-scavenging activity of the <3 kDa fraction was exerted by sub-fractions with low molecular weight. The highest reducing power was found in a sub-fraction containing peptides rich in Arg, Tyr and Phe. Both free amino acids and low molecular weight peptides thus seemed to contribute to the antioxidative activity of the peptide fractions, and Tyr seemed to play a major role in the antioxidant activity.